Draft Annual Plan 1975-76 Vol. I (Part I) Government of Manipur - Planning Commission (Planning Commission, 1974)
The newly emerged State of Manipur in the extreme North-East of India is still economically backward despite the efforts made, during the four successive Five Year Plans. Until recently, the socio-economic development of the State remained, by and large stagnant and even to-day many more milestones ails yet to be covered to. Remove the regional imbalances. The modest outlays of Rs. 1.55 crores, Rs. 6.25 crores and Rs. 2.88 cores during the first, second and the third Five Year Plans respectively and the still more modest expenditures of Rs. 103 crores, Rs. 5 97 crores and Rs. 12.81 crores respectively were systematic of the slow rate of economic growth. The same trend was noticeable during the three Plan years during 1966-67,1967-68 –and 1968—69 the outlays of Rs. 3.50 crores, Rs. 2.90 crores and Rs. 3.72 crores respectively.
Government of Manipur
Planning & Development Department
Keywords: State’s Resources; Sectoral Programmes; Agriculture & Allied Sectors; Problems facing the State; Comparison of National Income With State Income; Current Social Economic Situation; Statistics; Evaluation machinery; Planning; Notified Areas; Hill District Councils; Public Administration Buildings; Jail Buildings; Police Housing; Miscellaneous.